Keterbukaan dalam Pemeriksaan Perkara di Persidangan: Perspektif Hukum Acara Perdata - Nabilla Azzahra; Fauziah Lubis; Nasywa Nur Zhafira; Alyafi Afwa; Rajakqu Aulia; Fikri Fikri (Pusat Riset dan Inovasi Nasional, 2025)
This research examines the implementation of the principle of openness in the examination of cases in civil court proceedings in Indonesia, focusing on two main issues: (1) how the principle of openness is regulated and applied in civil court practices, and (2) what key obstacles hinder the implementation of this openness. The purpose of the study is to provide an in-depth overview of the mechanisms for implementing the principle of openness in the civil judicial process and to identify inhibiting factors that need to be addressed promptly in order to make the judicial system more transparent and accountable. This study employs a normative juridical method with a statutory and conceptual approach. Data were obtained through literature review, including legislation, legal doctrines, and relevant court decisions, and analyzed using a descriptive-analytical method. The findings indicate that the principle of openness is well accommodated normatively within Indonesia’s civil judicial system; however, its implementation still faces significant challenges, such as limited supporting facilities, inadequate dissemination among judicial officers, and the tension between protecting the privacy of parties and ensuring public access to information. To address these issues, improvements in technological infrastructure, human resource training, and internal policy revisions are essential steps to optimize the principle of openness in civil court proceedings.